2001
DOI: 10.1289/ehp.01109675
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to low doses of bisphenol A affects body weight, patterns of estrous cyclicity, and plasma LH levels.

Abstract: The nonsteroidal estrogenic compound bisphenol A (BPA) is a monomer used in the manufacture of polycarbonate plastics and resins. BPA may be ingested by humans as it reportedly leaches from the lining of tin cans into foods, from dental sealants into saliva, and from polycarbonate bottles into their contents. Because BPA is weakly estrogenic--approximately 10,000-fold less potent than 17beta-estradiol--current environmental exposure levels have been considered orders of magnitude below the dose required for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
228
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(251 citation statements)
references
References 53 publications
19
228
2
2
Order By: Relevance
“…The perinatal low-dose BPA exposure had no obvious effect on the reproductive physiology of their offspring, as deduced by observations of anogenital distance, puberty onset, ovarian histology and vaginal smears, in agreement with the literature regarding low-dose exposures (Ashby 2001, Rubin et al 2001, Tinwell et al 2002, Yoshida et al 2004, Patisaul & Polston 2008, Poimenova et al 2010. However, the reduced male:female offspring ratio in BPA-treated dams, though not statistically significant in this study, may imply a male embryo selective vulnerability in utero that worth further investigation.…”
Section: Reproductive Physiologysupporting
confidence: 90%
“…The perinatal low-dose BPA exposure had no obvious effect on the reproductive physiology of their offspring, as deduced by observations of anogenital distance, puberty onset, ovarian histology and vaginal smears, in agreement with the literature regarding low-dose exposures (Ashby 2001, Rubin et al 2001, Tinwell et al 2002, Yoshida et al 2004, Patisaul & Polston 2008, Poimenova et al 2010. However, the reduced male:female offspring ratio in BPA-treated dams, though not statistically significant in this study, may imply a male embryo selective vulnerability in utero that worth further investigation.…”
Section: Reproductive Physiologysupporting
confidence: 90%
“…However, irregular estrous cyclicity could not be detected in our BPA study in which animals were exposed to 3000 ppm (corresponding to 231.8 mg/kg per day during the gestational period and 384.4 mg/kg per day during the lactation period). A similar lack of effects on estrous cyclicity was reported by others using rats or mice (Kwon et al 2000;Suzuki et al 2002) at doses much higher than those of Rubin et al (2001). Differences in the exposure time-windows or exposure protocols do not appear to be responsible for the discrepancy, because Kwon and colleagues selected a wide time window for exposure similar to that of Rubin and coworkers, and Suzuki and colleagues chose the more potent subcutaneous injection route.…”
Section: Discussionmentioning
confidence: 55%
“…Although as an estrogenic reference drug EE exposure at 0.5 ppm exerted obvious endocrine effects on offspring, neither BPA nor NP, even at doses causing maternal toxicity, did not affect development of the endocrine/reproductive systems. Rubin et al (2001) reported that maternal perinatal exposure to BPA induced irregular estrous cyclicity in rats at a dose level corresponding to 1.2 mg/kg per day in the drinking water from GD 6 to PND 22. However, irregular estrous cyclicity could not be detected in our BPA study in which animals were exposed to 3000 ppm (corresponding to 231.8 mg/kg per day during the gestational period and 384.4 mg/kg per day during the lactation period).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in rodent models have reported that perinatal exposure to BPA increases the body weight of offspring at 6 months of age (Alonso-Magdalena et al 2010) and in adulthood (Somm et al 2009) as well as in the neonatal period (Howdeshell et al 1999, Rubin et al 2001, Rubin & Soto 2009). However, Ryan et al (2010) reported a contrary result that oral exposure to BPA during the perinatal period did not induce glucose intolerance later in life in CD-1 mice.…”
mentioning
confidence: 99%